IoT system to monitor the well-being of senior citizens who self-isolate during the pandemic - Gonçalves, Fábio (2021)
The COVID-19 pandemic and the need for selfisolation has decreased the frequency of visits to senior citizens by family members or caregivers. Because of this, many health concerns of the elderly remained unresolved. We created a IoT system, called Zelar@CB, that monitors the daily activities of isolated elderly people who do not have access to at-home care. The proposed project detects unusual activity by monitoring the person’s usage of electrical appliances to track if the user left the stove on or if there is a change in usage. It can also detect when the user falls, and sends an alert to family members or caregivers.